Poetry and Poetics: some critical-creative reflections (Itinera, 2022)
Christopher Norris is Emeritus professor at Cardiff University. Recently, he began to address philosophical questions through poetry. In his paper, he explains why. Rather than expressing definite ideas in an elegant way, poetry can be intended as a process from which new ideas (also philosophical ones) can emerge. The result are a number of poems which cover a variety of issues, ranging from philosophy to politics, arts, history of ideas and science. Itinera has already begun to publish a few of these poems in previous issues and is now presenting three of them on painters (Turner, Matisse, Magritte).